Combustion synthesis and electrochemical evaluation of Cr-substituted lithium vanadium (III) phosphate. (February 2019) - Rezqita, Arlavinda; Stankov, Simeon; Kahr, Jürgen; Hamid, Raad; Gocheva, Irina; Trifonova, Atanaska
In this work, the effect of Cr 3+ partial substitution on vanadium site in monoclinic lithium vanadium(III) phosphate (LVP) structure resulting in compounds with general formula: Li3 V2 - x Cr x (PO4 )3 -C ( x = 0, 0.05, 0.1, 0.15) was studied. A two-step sol-gel combustion method was employed in syntheses. The samples were characterized by X-ray powder diffraction, scanning electron microscopy, coupled plasma optical emission spectroscopy, and flash combustion. The electrochemical performance of the active materials was examined through rate capability tests and cyclic voltammetry. The unsubstituted compound LVPC delivers higher capacity compared to the Cr-containing samples due to chromium inactivity in the potential range 3.0–4.4 V vs. Li/Li + . However, the Cr-substituted materials show better overall capacity retention (97–97.6%) in contrast to Li3 V2 (PO4 )3 -C (96%) in long cycling.